Service outsourcing strategy decision for value creation in manufacturing firms - Jianqiang Luo; Zichao Yang; Qinhong Zhang; Rongrong Pan (Journal of Management Science and Engineering, 2022)
This study aims to resolve the difficult problem of manufacturers’ service outsourcing strategy decision-making, with services divided into two types: hygienic and motivational. We build a value creation model for the manufacturer, service contractor, and customer under different outsourcing strategies, and we examine optimal outsourcing decision-making in various scenarios and its effect on the value creation of related entities. The results indicate that motivational services have a lower bound characterized by service utility. When the manufacturer derives services higher than this lower bound, it should operate its own motivational service and outsource the hygienic service to create greater value. When the manufacturer is limited by resources or capabilities and is required to outsource the motivational service, it can maintain value creation by setting an appropriate contract coefficient. The service contractor should undertake motivational services within the contract boundary negotiated by the manufacturer and conduct hygienic services outside the boundary. Theoretically, outsourcing both service types can maximize customer value, but this may not achieve the manufacturers’ optimal value creation.